The impacts of supply disruptions and dynamic pricing on a continuous-review inventory system with price-sensitive customer demands. (17th October 2012) - Chen, Yuerong; Wang, Shengyong
This paper considers an inventory system that consists of a supplier, a retailer, and customers. The retailer adopts a continuous-review inventory policy, applies dynamic pricing and is subject to supply disruptions. Customer demands are price-sensitive. The inventory system is simulated and the impacts of supply disruptions and dynamic pricing are investigated. The experimental results provide managerial suggestions to the retailer. For instance, the retailer should pay more attention to supply disruption duration than disruption frequency. Besides, the retailer ought to consider the scenarios of supply disruptions and customer demand variation before making a dynamic pricing strategy.